Extracellular Vesicles as Therapeutic Agents for Cardiac Fibrosis - Rogers, Russell G.; Ciullo, Alessandra; Marbán, Eduardo; Ibrahim, Ahmed G. (Frontiers in Physiology, 2020)
Heart disease remains an increasing major public health challenge in the United States and worldwide. A common end-organ feature in diseased hearts is myocardial fibrosis, which stiffens the heart and interferes with normal pump function, leading to pump failure. The development of cells for regenerative therapy has been met with many pitfalls on its path to clinical translation. Recognizing that regenerative cells secrete therapeutically bioactive vesicles has paved the way to circumvent many failures of cell therapy. In this review, we provide an overview of extracellular vesicles, with a focus on their utility as therapeutic agents for cardiac regeneration. We also highlight the engineering potential of extracellular vesicles to enhance their therapeutic application.